(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Ensuring and maintaining of optimum microclimate in pigsties is an energy intensive process. The paper presents an analysis of the possibilities how to cut the consumption of energy and save the fossil fuel by improving thermal endurance of building structures, returning a part of heat emitted together with the exchanged air during ventilation and by burning biogas produced as a result of the anaerobic processing of manure. It has been clarified that at positive outdoor air temperatures heat recuparators can ensure 75-100 W heat supply per pig of an average live mass of (70 kg), which fully covers the heat deficiency required for normal microclimate. Burning biogas produced as a result of anaerobic processing the manure from pigs of average live mass can ensure average heat energy of 20-30 W for heating the pigsty, which covers only a part of the heat requirements in the cold weather periods. Draft proposals have been elaborated for the anaerobic processing of the production wastes in a pigsty for 4000 sows. The generated energy covers about 60 % of the annual energy consumption in a pigsty. The significance of implementing the draft is emphasized by the effect in an environmental and ecological aspect.